2014 IEEE Frontiers in Education Conference (FIE) Proceedings 2014
DOI: 10.1109/fie.2014.7044380
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of agile methodologies for software and product development in a capstone design project

Abstract: Professional skills are often emphasized in a capstone engineering design course, especially in relation to addressing ABET Engineering Criteria. Learning of these skills is typically a product of the project management approach followed by design teams. The principles behind agile development and the features of the Scrum methodology match up well with the expected outcomes of a major engineering design experience and preparation needed by students for engineering practice. This paper presents a case study on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
1
13
0
1
Order By: Relevance
“…Numerous recent articles focus on Agile practices in education, e.g., [15,10,17,2], which indicates the will and the need to teach students this methodology, especially in Computer Science and Information Technology. These articles show that the use of Agile methods in educational activities has very positive effects.…”
Section: Agile Methodology In Educationmentioning
confidence: 99%
“…Numerous recent articles focus on Agile practices in education, e.g., [15,10,17,2], which indicates the will and the need to teach students this methodology, especially in Computer Science and Information Technology. These articles show that the use of Agile methods in educational activities has very positive effects.…”
Section: Agile Methodology In Educationmentioning
confidence: 99%
“…These authors found that after implementation of this feedback system, negative team outcomes (personality conflicts, social loafing) were eliminated and the quality of the design team deliverables improved. In another study 29 , the use of agile project management for a two-semester senior design project is documented by profiling the experience of the student design team, client, and faculty mentor. The agile project management framework required the student team to work in two-week "sprint" iterations, where each sprint contained a deliverable, followed by a progress meeting with the client and mentor.…”
Section: Source and Destinationmentioning
confidence: 99%
“…Over the last few years, a number of studies reported experience about the use of both traditional waterfall plan driven and agile driven approaches for software engineering capstone course [1][2][3][4][5]. Rover et al [6] presented a case study of developing software applications in two-semester senior project. They found that the use of Agile was successful and beneficial.…”
Section: Introductionmentioning
confidence: 99%